Understanding of coaches with young athletes - B.G. Kedrovskiy; O.G. Shalar; A.V. Grinevich (Physical Education of Students, 2013)
The problems of understanding coaches athletes with athletes. It is studied orientation of the individual coaches. It is studied their job satisfaction and how to respond to situations of conflict. The study involved 4 coaches in athletics of varying skill levels, and 64 athletes. Found that all the athletes are sociable, communicative, able to listen, which correspond to a high level (0.6-2.1%). Athletes appreciate their coaches sensitivity, kindness, friendliness. It was found that the rate of burnout is very low (18% to 26%) of all the coaches, which indicates emotional stability trainers, strong enough foundation for their functionality. It is shown the availability of coaches and athletes joint features. Almost all of the coaches and athletes are a temperamental group of extroverts are strong, energetic and emotionally stable individuals. This fact greatly facilitates relationships and encourages productive collaboration.